Comparison of Amplitude and Implicit Time Between Jet Electrode, Dencott Electrode and Dawson-Trick-Litzkow Electrode in Multifocal Electroretinography Examination in Adult - Syntia Nusanti; Ika Citra Susanti; M. Sidik; Aria Kekalih (Indonesian Vitreoretinal Society, 2022)
Introduction: Multifocal electroretinography (ERG) is an examination which measures retinal electrical activity as a response to lighting stimulus and allows simultaneous recording in many topographic locations. Various electrodes have been developed to balance examination accuracy and also patients’ comfort. The objective of this study is to establish normal values of multifocal ERG and to compare the values and the comfort level using Jet, Dencott and DTL electrode in Indonesian Adult. Methods: Through convenient sampling 49 normal Indonesian subjects between 19 and 49 years old were selected. Multifocal ERG amplitudes and implicit time values were measured according to recommendation by the ISCEV. Evaluation consisted of N1 and P1 wave in ring 1 to 5. after the examination, all subjects filled in a questionnaire about comfort level, adopted from the visual analog scale. Result: We observed a statistically significant difference in multifocal ERG normal values between electrode with higher wave amplitudes and longer implicit time in Jet and Dencott electrodes compared to DTL electrodes. Jet and DTL electrodes are more comfortable than Dencott electrodes for Indonesian adults in multifocal ERG. Conclusion: DTL electrodes give the lowest wave amplitude and the shortest implicit time and are the most comfortable electrode compared to Jet and Dencott electrodes, in multifocal ERG in Indonesian adults.